Relationship between addictions and obesity, physical activity and vascular aging in young adults (EVA-Adic study): a research protocol of a cross-sectional study - Vicente-Gabriel, Sara; Lugones-Sánchez, Cristina; Tamayo-Morales, Olaya; Vicente Prieto, Alberto; González-Sánchez, Susana; Conde Martín, Sandra; Gómez-Sánchez, Marta; Rodríguez-Sánchez, Emiliano; García-Ortiz, Luis; Gómez-Sánchez, Leticia; Gómez-Marcos, Manuel A.; , EVA-Adic Investigators Group; et al. (Frontiers in Public Health, 2024)
Background Behavioral and substance addictions are prevalent health problems that, alongside obesity, are linked to reduced physical activity and increased sedentary time. Similarly, arterial stiffness and vascular aging are processes that begin gradually at an early age and are closely associated with morbidity and mortality from cardiovascular diseases. The main objective of this study is to analyze how addictions are related to obesity and body fat distribution, physical activity, sedentary time, arterial stiffness and vascular aging, as well as sleep quality, cognitive function and gender differences in young adults aged between 18 and 34 years. Methods This cross-sectional descriptive observational study will analyze data from 500 subjects (250 men and 250 women) aged 18–34 without cardiovascular disease, selected by simple random sampling with replacement from the urban population of the city center of Salamanca (34,044 people aged 18–34, with 18,450 women and 15,594 men). Behavioral and substance addictions, as well as sleep quality and cognitive impairment will be assessed using questionnaires. The Pittisburg Sleep Quality Index (PSQI) will be used to measure sleep quality and the Ford questionnaire will be used to measure insomnia in response to stress. For obesity, weight, height, waist and hip circumference, body composition will be measured with the Inbody 230® impedance meter. For physical activity and sedentary time, we will use the Actigraph® accelerometer alongside the international physical activity questionnaire (IPAQ) and the Marshall questionnaire. The Sphygmocor System® will be used for pulse wave analysis and carotid-femoral pulse wave velocity (cfPWV), while the Vasera VS-2000® will measure cardio ankle vascular index (CAVI) and brachial-ankle pulse wave velocity (baPWV). Vascular aging will be calculated with the 10th and 90th percentiles of cfPWV or baPWV. Demographic, analytical variables will be collected, as will data to assess vascular, cardiac, renal, and brain injury. Discussion Addictions are on the rise in today’s society, affecting the mental health and well-being of those who suffer from them, generating important social problems such as job loss, family dysfunction, debt and social isolation. Together with obesity, they are prevalent health problems in young adults and are associated with lower physical activity and higher sedentary time. Meanwhile, arterial stiffness and vascular aging are processes that begin gradually at an early age and determine morbidity and mortality caused by cardiovascular diseases. The results of this project will allow us to understand the situation regarding behavioral and substance addictions in young adults. Better understanding of these addictions will in turn facilitate the development of more effective prevention strategies and intervention programs, which can then reduce the negative impact at both the individual and societal levels. Clinical trial registration [ClinicalTrials.gov], identifier [NCT05819840].